Constituintes Químicos de Hyptidendron canum R. Harley (Lamiaceae) - Lemes, Geralda de Fátima; Ferri, Pedro Henrique; Lopes, Márcia Nasser [UNESP] (My University, 2011)
CHEMICAL CONSTITUENTS OF Hyptidendron canum (Pohl ex Benth.) R. Harley (LAMIACEAE). Chemical investigation of Hyptidendron canum stems resulted in the isolation of betulinic, ursolic and euscaphic acids. From the leaves were isolated 3β-O- β-galactopiranosilsitosterol, ursolic aldehyde, and mixtures of maslinic acid and 2α-hydroxyursolic acid, α and β-amyrin, uvaol and erythrodiol, sitosterol and stigmasterol, spathulenol and globulol. Hexane and chloroform leave fractions as well as ursolic and betulinic acids showed antifungal activities against the yeast form of Paracoccidioides brasiliensis.
Keywords: Hyptidendron canum; triterpenes; antifungal activity